C*-Algebra Valued Fuzzy Soft Metric Spaces and Results for Hybrid Pair of Mappings - Daripally Ram Prasad; Gajula Naveen Venkata Kishore; Hüseyin Işık; Bagathi Srinuvasa Rao; Gorantla Adi Lakshmi (Axioms, 2019)
In this paper, we establish some results on coincidence point and common fixed point theorems for a hybrid pair of single valued and multivalued mappings in complete <semantics> C * </semantics> -algebra valued fuzzy soft metric spaces. In addition, we provided some coupled fixed point theorems. Finally, we have given examples which support our main results.